The Relationship Between Embodied Intelligence and the Cooperative Ability of Grade 2 Elementary School Students - Nurdiansyah, Alvin; Persada, Yuris Indria; Mardhatillah, Mardhatillah (Teunuleh Publisher, 2024)
The purpose of this study is to find out the relationship between emotional intelligence and the ability to work together in 2nd grade elementary school students. The approach used is quantitative with data collection through questionnaires to determine the emotional intelligence and cooperative ability of grade 2 elementary school students. The results of this study showed that there was a positive relationship between emotional intelligence and cooperation ability had a Pearson correlation = 0.335. However, the relationship between the two is not significant, as evidenced by the results of the linearity regression test of 0.081. Emotional intelligence can explain 11.2% variability in student cooperation. This research suggests the development of emotional intelligence in elementary school education to improve empathy, sympathy, and social skills. In addition, further research is recommended to examine other factors that affect students' ability to cooperate.